Atenolol and bendrofluazide in hypertension. Issue 5989 (18th October 1975) - Petrie, J C; Galloway, D B; Webster, J; Simpson, W T; Lewis, J A
Abstract : The effect of atenolol, a new beta-1-adrenergic receptor blocking agent, was studied in a double-blind cross-over trial in 24 carefully selected hypertensive outpatients. After a four-week run-in period on matching placebo each patient received atenolol 200 mg/day, atenolol 400 mg/day, a combination of atenolol 200/mg day with bendrofluazide 5 mg/day, and bendrofluazide 5 mg/day alone, according to a random sequence. Atenolol at either dose produced a significantly greater reduction in all blood pressure levels except standing systolic pressure than bendrofluazide alone. There was no statistically significant difference between the effects of the two atenolol doses on either blood pressure or pulse rate. The addition of bendrofluazide to atenolol resulted in a further significant lowering of the blood pressure. A significant effect of thiazide on weight was noted. The study shows that atenolol, a cardioselective beta-blocker of similar potency to propranolol in animals but without membrane-stabilizing or partial agonist acitivity, is an effective and well-tolerated hypotensive agent.